Access to and Reactivity of Fe0, Fe−I, FeI, and FeII PCcarbeneP Pincer Complexes. Issue 33 (9th July 2021) - Wang, Qingyang; Manzano, Richard A.; Tinnermann, Hendrik; Sung, Simon; Leforestier, Baptiste; Krämer, Tobias; Young, Rowan D.
Abstract: Despite their promising metal–ligand cooperative reactivity, PCcarbene P pincer ligands are rarely reported for first‐row transition‐metal centres. Using a dehydration methodology, we report access to an Fe 0 PCcarbene P pincer complex (1 ) that proceeds via an isolated α‐hydroxylalkyl hydrido complex (3 ). Reversible carbonyl migration to the carbene position in 1 is found to allow coordination chemistry and E−H bond addition (E=H, B, Cl) across the iron–carbene linkage, representing a unique mechanism for metal–ligand cooperativity. The PCcarbene P pincer ligand is also found to stabilize formal Fe II, Fe I, and Fe −I oxidation states, as demonstrated with synthesis and characterization of the complexes [11‐X ][BAr F 20 ] (X=Br, I), 12, and K[13 ]. Compound K[13 ] is found to be highly reactive, and abstracts hydrogen from a range of aliphatic C−H sources. Computational analysis by DFT suggests that the formal Fe I and Fe −I complexes contain significant carbene radical character. The ability of the PCcarbene P ligand scaffold to partake in metal–ligand cooperativity and to support a range of iron oxidation states renders it as potentially useful in many catalytic applications. Abstract : We report access to an Fe 0 PCcarbene P pincer complex that proceeds via an isolated α‐hydroxylalkyl hydrido complex. Reversible carbonyl migration to the carbene position is found to allow coordination chemistry and E−H bond addition (E=H, B, Cl) across the iron–carbene linkage, representing a unique mechanism for metal–ligand cooperativity. The PCcarbene P pincer ligand is also found to stabilize formal Fe II, Fe I and Fe −I oxidation states.